Avaliação de risco baseada na metodologia do plano de segurança da água: estudo de caso da ETA do município de Viana-ES e pontos de captação de água bruta - Vargas, Marcio Nolasco (2019)
The application of risk assessment in Water Supply Systems (WSS) according to the principles of the Water Safety Plan (WSP) is described in Ordinance Nº. 5/2017, Annex XX, of the Ministry of Health (MH). Such a risk assessment aims to ensure the quality of drinking water for human consumption. To this end, the World Health Organization (WHO) introduced basic concepts that underline the importance of conducting risk assessment throughout the SAA, from capture to the final consumer. This master's research addresses a case study of the Water Treatment Plant (WTP) in the municipality of Viana-ES, Brazil, and its two collection points (Santo Agostinho river and Formate river). Two risk assessments were performed based on the semi quantitative risk characterization methodology. In the first assessment, checklists were applied to identify possible structural hazardous events and the risk sequence was characterized. The second evaluation sought to characterize the risk of some parameters used as indicators of drinking water quality described in the Ordinance of MH Nº. 5/2017 (Annex XX), which also carried out an analysis of drinking water statistical data in January. from 2015 to December 2018. The indicators studied were turbidity, free residual chlorine, fluoride ion, Total Coliforms (TC) and Escherichia coli (E. coli), and disinfection by-products. The proposed methodology was based on the guidelines presented in the WSP Manual - Step by Step Risk Management for WHO and International Water Association (IWA) drinking water providers. The results of the risk ratings were consolidated into two tables, called the “risk scoreboard”. The structural assessment risks obtained more critical risk grades than the potability parameters risk assessment results. However, it was concluded that the structural risks do not directly affect the water quality at the treatment exit. Since the risks of the parameters were low, except for two parameters characterized as medium risk (TC/ E.coli and total haloacetic acids). Finally, it is concluded that the WHO and IWA guidelines were quite relevant for the application of the risk assessment methodology and description of the study area